Efficiency of Buttress Form on the Out-of-plane Resistance of Masonry Walls Subjected to Vault Thrust - Avcil, Fatih; Izol, Rabia; Guerel, M. Arif; Arkan, Enes; Mollamahmutoglu, Cagri (UNIV OSIJEK, TECH FAC, 2023)
Many historical buildings are covered with vaults or domes. This study investigates the effectiveness of the buttress form on the lateral (out-of-plane) resistance of masonry walls subjected to the inclined vault thrust. For this purpose, a basic calculation model was created from an existing historical masonry building. Calculation models were obtained by adding buttresses which have various forms but equal volumes to this model. In addition to the most commonly rectangular, trapezoidal, and triangular buttresses, two-stepped, concave curvilinear, and semi-cylindrical buttresses were also considered. Nonlinear static analyses were performed on the models with Abaqus software. By considering one side (half) of the calculation models, inclined thrust force versus wall top section lateral displacement graphs were obtained, and the effectiveness of the buttress form on the lateral resistance of the building was determined. It has been observed that the structure has the highest out-of-plane resistance (5700 kN and 5431 kN) when supported by triangular and curvilinear concave buttresses, respectively, and the lowest resistance (1549 kN) when supported by semi -cylindrical buttresses. In the study, the effects of three parameters, depth, thickness and height of the buttress, on the lateral resistance of the building were also investigated by considering only the rectangular buttressed model. These parameters were found to have significant effects on the resistance as expected.
Keywords: buttress form; inclined thrust; lateral resistance; nonlinear static analysis; vault; Engineering